ANALISIS PENGARUH RISIKO KREDIT, RISIKO PASAR DAN MODAL TERHADAP RETURN SAHAM PERBANKAN - B11110003, Jurianti (Jurnal Manajemen Update, 2014)
This study aimedtoexamine the effect ofcredit risk, as measured by Non-Performing Loans(NPL), the marketriskas measured by theNet Interest Margin (NIM) andcapitalas measured byAdequancyCapitalRatio(CAR) of thebankstock returnslistedinthe Indonesia Stock Exchangethe period 2010-2012. Study is aform ofquantitativeresearch. With atotal population of32banks listedon theIndonesia Stock Exchange period2010-2012. Samplesweretakenusing purposive sampling techniqueis the determination ofthe samplewithparticularconsiderationto thetotal sample of27 banks. The data usedaresecondary datafromwww.idx.co.id.Analysis of datausing multiple regression analysis. Based onmultiple regression analysisshowedthat theNon-Performing Loan(NPL) has apositivevalueandno significant effecton stock returnsbyvaluetcount1,564less than thevalue ttabel1,992.Net Interest Margin(NIM) has apositivevalueandno significant effecton stock returnswith avalue of0.952tcountsmaller than thevalue ttabel1,992. ForCapitalAdequacy Ratio(CAR) has anegative valueandno significant effecton stock returnswith a value of-0.594tcountgreaterthanthe value of-1.992ttable. Based on the resultsof the analysisshould betheinvestors inthe investmentanalysisshouldalsoperformfundamental analysisas a complement totechnical analysisin makinginvestment decisions. Keywords: Credit Risk, Market Risk, Capital, Stock Return